PENGARUH PESAN AKUN INSTAGRAM @KETIMBANG.NGEMISBEKASI TERHADAP KEPEDULIAN GENERASI MUDA - SURANTI YUNIDAR; KARTINI ROSMALAH D. K. (Interpretasi: Communication & Public Relations, 2020)
The poverty that ensnares the elderly should get a more crucial treatment from the government. Through this account "Rather than Ngemis Bekasi'', the elderly who are trapped in poverty and far from the government's attention are eventually raised in the public. The research method used a survey method with an explanatory descriptive quantitative approach. The sample of this research is the younger generation who follow on Instagram @ketimbang.ngemisbekasi. The research method of this study is a survey method with an explanatory descriptive quantitative approach. The sample of this research is Accidental Sampling. Data collection techniques using questionnaires and interviews. The results of the study prove that 62.8% of the younger generation's concern for the elderly are influenced by messages in the @ Instagram account rather than socializing such as uploading photos/videos, captions, likes, comments, each of which can affect knowledge (cognitive), emotions (affective), and real behavior (conative) of respondents. The rest, 37.2%, is influenced by other factors such as motivation within themselves, family environment, community environment, and social closeness. The suggestions that the researchers give to the next researcher, it is better to learn more about other theories related to the influence of social media messages such as the uses- and-gratifications theory, which can use qualitative methods and add other variables that have not been studied in this study